Involvement of Steroid Hormones, Corticosterone and Testosterone, in Synthesis of Heat Shock Proteins in Broiler Chickens - Wang, S.; Edens, F.W. (International Journal of Poultry Science, 2008)
Large comb (LC) broiler cockerels, with high levels of testosterone and corticosterone, survived acute heat stress while small comb (SC) cockerels, with low levels of testosterone and corticosterone were more susceptible to heat stress and suffered higher mortality rates. This phenomenon was related to the greater ability of the LC and the lesser ability of the SC broilers to synthesize heat shock proteins (HSP), which are involved in acquisition and maintenance of thermotolerance. When broiler cockerels, selected for LC or SC, were exposed to acute heat stress, the synthesis of three HSP-hsp-90, hsp-70 and hsp-23 by peripheral blood leukocytes was elevated in both groups of broilers, but LC chickens responded with higher HSP synthesis than did SC chickens. One of the normal cellular proteins, actin, was depressed during the heat stress over 105 minutes. To determine whether steroid hormones, testosterone and corticosterone, influence the expression of HSP in chickens, exogenous testosterone and corticosterone were implanted in LC capons and metyrapone-fed LC capons, respectively. The plasma testosterone was raised in the testosterone-treated capons, was depressed in the capons and metyrapone-fed capons and was indicated indirectly by growth rate of the comb. The heat-induced synthesis of HSP was depressed by caponization and depressed further in the capons fed metyrapone, which blocks the synthesis pathway of endogenous corticosterone in adrenal glands. The exogenous testosterone and to a lesser degree, corticosterone, stimulated the expression of HSP in heat-stressed capons. The results suggested that the steroid hormones, testosterone and corticosterone, are involved in the expression of HSP, which are associated with acquired and maintained thermoresistance in domestic chickens.